Аномальный фотовольтаический эффект в структуре с барьером Шоттки – Мотта - Karimov, A. V.; Yodgorova, D. M.; Saidova, R. A.; Giyasova, F. A. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
The paper presents the results of a study of a photovoltaic effect observed at room temperature, which is accompanied by a change in the sign of the photocurrent when transitioning from the region of intrinsic absorption to the impurity region within the spectral range of 0.4–2 μm in an oxygen‑doped double‑base Ag–N0AlGaAs–n+GaAs–n0GaInAs–Au structure. Such structures are of interest for fiber‑optic systems.